2019
DOI: 10.1007/s42452-019-0974-6
|View full text |Cite
|
Sign up to set email alerts
|

Solvation thermodynamic parameters for sodium dodecyl sulfate (SDS) and sodium lauryl ether sulfate (SLES) surfactants in aqueous and alcoholic-aqueous solvents

Abstract: Conductivity of sodium dodecyl sulfate (SDS) and sodium lauryl ether sulfate (SLES) surfactants in aqueous and in alcoholic-aqueous mixed solvents (methanol, ethanol, and glycerol) with different mole fractions of alcohols has been measured experimentally at different temperatures (298.15, 303.15, 308.15 and 313.15 K). Surface tension was also measured experimentally for SDS and SLES in aqueous solution at 298.15 K. Critical micelle concentration (CMC) of both SDS and SLES was determined from the measured con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…The surface tension is obtained by the integral of the difference between the diagonal components of the pressure tensor γ = − b z ( P xx + P yy – 2 P zz )/4 where b z is the length of the simulation box along the z axis, and P xx , P yy , and P zz are the principal components of the pressure tensor . As shown in Figure S1, the surface tensions obtained from liquid/vapor interface simulations are in good agreement with experimental results. , Experimental data for other systems were not reported in the literature to the best of our knowledge. Therefore, comparison of simulated results with experiments is not possible.…”
Section: Methodssupporting
confidence: 74%
See 1 more Smart Citation
“…The surface tension is obtained by the integral of the difference between the diagonal components of the pressure tensor γ = − b z ( P xx + P yy – 2 P zz )/4 where b z is the length of the simulation box along the z axis, and P xx , P yy , and P zz are the principal components of the pressure tensor . As shown in Figure S1, the surface tensions obtained from liquid/vapor interface simulations are in good agreement with experimental results. , Experimental data for other systems were not reported in the literature to the best of our knowledge. Therefore, comparison of simulated results with experiments is not possible.…”
Section: Methodssupporting
confidence: 74%
“…28 As shown in Figure S1, the surface tensions obtained from liquid/vapor interface simulations are in good agreement with experimental results. 29,30 Experimental data for other systems were not reported in the literature to the best of our knowledge. Therefore, comparison of simulated results with experiments is not possible.…”
Section: Methodsmentioning
confidence: 99%
“…In a related study [41], the addition of ethanol to the acceptor medium, in order to enhance the solubility of the released substance in the acceptor medium was recommended. Moreover, in a study by Farid et al [42], it has been shown that in ethanol/water mixtures the critical micellar concentration of SDS increases with the increasing ethanol concentration. Therefore, the use of ethanol at a concentration of 80% as an acceptor medium precluded the potential risk for solubilization of vitamin E in the acceptor medium, which could affect the detected amount of vitamin E released.…”
Section: Vitamin E Release Kineticsmentioning
confidence: 96%
“…The variation of the CMC with chemical and physical parameters provides a perfect view for the nature of the surfactant self-association. Methods for CMC determination include conductivity, viscosity, surface tension, ion activity, dye incorporation, gel filtration spectrophotometrically, counterion magnetic resonance, and refractive index measurements. Solvation of different cationic surfactants in different solvents was investigated before, where CMC was measured with different methods. Also, density, refractive index, and UV spectra measurements of solutions are expected to shed some light on the solute–solvent interactions and configuration of their mixtures. Other thermodynamic properties including molal volume, ionic association, and polarizability were investigated for ionic liquids, , especially for imidazolium ionic liquid surfactants. …”
Section: Introductionmentioning
confidence: 99%